Clinical Review and Prognostic Analysis of α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionate Receptor-Associated Encephalitis - Wang, Kemo; Shi, Yanting; Du, Qianwen; Zhang, Ran-ran; Wu, Huaikuan; Qiao, Shan; Liu, Xuewu (Frontiers in Neurology, 2021)
Purpose: Autoimmune encephalitis (AE) is a heterogeneous neurological autoimmune disorder associated with cognitive and psychiatric symptoms. It can be divided into several subtypes based on autoantibodies. Anti-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor encephalitis (AMPAR-E) is one of the recently discovered AE subtypes, usually manifesting limbic encephalitis and with a good prognosis. Considering AMPAR-E has been described for the first time, only a few cases with similar antibodies have been reported clinically. We aimed to clarify the clinical course and prognosis of the disease in the light of previous reports. Patients and Methods: We collected data on the diagnosis and treatment of six cases of AMPAR-E, diagnosed at the Qilu Hospital of Shandong University in the past 5 years. We retrospectively analyzed the clinical characteristics of the patients and performed a follow-up of the disease. Results: The patients often presented with limbic encephalitis, which sometimes coexisted with tumors. In addition, immunotherapy had a significant effect on the disease. The clinical outcome was related to factors such as the age of onset, timing of treatment, and presence of tumors. Conclusion: In conclusion, specific antibody tests should be performed as early as possible in suspected cases. Clinicians should actively administer immunotherapy and the management of the co-tumor. In addition, repeat antibody tests and image examinations following discharge from the hospital guide the maintenance protocol of immunotherapy.